2022
DOI: 10.1088/1742-6596/2165/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of CTAB surfactant modified TiO2 nanoparticles as antibacterial fabric coating material

Abstract: TiO2 preparation has been carried out with the addition of cetyl trimethyl ammonium bromide (CTAB) surfactant. The sol-gel method is used in the preparation of TiO2, where TiCl4 is used as a precursor. The resulting TiO2 was characterized using XRD, FTIR, XRF and SEM. XRD results show the crystal size of TiO2 17.75 nm with the rutile phase. The FTIR results show a broad absorption band between 800 and 400 cm−1 by Ti–O vibrations in the crystal lattice. The XRF results showed that the TiO2 content was 80.80%. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…As per the literature reports the fabrics functionalized with TiO 2 NPs have better antibacterial and physical properties [105]. Bukit et al [106] reported that the TiO 2 NPs prepared by sol-gel technique and functionalized with CTAB can be used as antibacterial material to be coated over fabrics. Also, it was reported that the TiO 2 NPs modified fabric displayed excellent antibacterial activity against both gram positive and gram negative bacteria owing to its catalytic activity.…”
Section: Zinc Oxide Nps (Zno Nps)mentioning
confidence: 90%
“…As per the literature reports the fabrics functionalized with TiO 2 NPs have better antibacterial and physical properties [105]. Bukit et al [106] reported that the TiO 2 NPs prepared by sol-gel technique and functionalized with CTAB can be used as antibacterial material to be coated over fabrics. Also, it was reported that the TiO 2 NPs modified fabric displayed excellent antibacterial activity against both gram positive and gram negative bacteria owing to its catalytic activity.…”
Section: Zinc Oxide Nps (Zno Nps)mentioning
confidence: 90%
“…The electrons are excited to the conduction band from the valence band leading to the generation of electron/ hole pair, and they consequently react with H 2 O and O 2 to generate ROS. 137,138 Singh et al 139 developed SH cotton fabric using polytriethoxyvinylsilane and polydimethylsiloxane along with AgBr NPs. The SH property was promoted by polytriethoxyvinylsilane and polydimethylsiloxane whereas the photocatalytic activity was induced by the presence of AgBr semiconductor.…”
Section: Photo Catalytic Activitymentioning
confidence: 99%
“…When the light with suitable energy is irradiated over the photocatalyst present on the SH surface, redox reactions occur. The electrons are excited to the conduction band from the valence band leading to the generation of electron/hole pair, and they consequently react with H 2 O and O 2 to generate ROS 137,138 . Singh et al 139 developed SH cotton fabric using polytriethoxyvinylsilane and polydimethylsiloxane along with AgBr NPs.…”
Section: Sh Fabricsmentioning
confidence: 99%